Design of integrated space-air-ground farmland quality monitoring mobile laboratory - ZHANG Feiyang (Agro-Environmental Protection Institute, Ministry of Agriculture, 2021)
China is facing a great challenge with grain demand. Meanwhile, the decline of farmland quality will affect the quality and safety of food. The existing methods of farmland quality monitoring are characterized by a long time period and a lack of detailed spatial information of farmland quality. They could not provide the data that meet the requirements of farmland quality monitoring. This study explored a new methods and mobile laboratory for farmland quality monitoring. A farmland quality monitoring indicator system consisting of the variables or predictors that can be fast measured spatially and temporally was first developed. In this study, a framework which integrated satellite remote sensing monitoring, unmanned aerial vehicle(UAV) monitoring, wireless sensor network(WSN) monitoring and in situ measurement method into a farmland quality monitoring mobile laboratory was built. This study also explored the integration of remote sensing, UAV, WSN and ground-based monitoring methods through middleware technologies that connect various components of the system. Moreover, this study developed of a farmland quality monitoring mobile laboratory with an optimal design of routines for fast collection of data. A on-site test was carried out in the area of farmland upgrade and reconstruction program, which took less than 2 hours to quick test 13 indicators for 5 sampling points showed higher efficiency and on-site analysis capability compared with traditional farmland quality monitoring method. This study overcame the gaps that currently exist in the traditional farmland quality monitoring methods, realized comprehensive and multi-scale monitoring of farmland quality, promoted the effectiveness of monitoring cultivated land, and enhanced the capacity of farmland management and protection.